Screening A. ventricosa populations for 2n gametes - Nikoloudakis, Nikolaos; Aissat, Assia; Katsiotis, Andreas (My University, 2018)
Sexual polyploidization via the formation of 2n gametes has been acknowledged as the most significant evolutionary mode of polyploidization among plant species. The present study was conducted in order to determine whether 2n gametes are present in the C-genome diploid Avena ventricosa Bal. ex Coss., a species that contributed to the evolution of the cultivated hexaploid species (Avena sativa L). Individual plants belonging to four different Cypriot populations, were screened for pollen grain size variation with the aim to distinguish 2n gametes. Avena ventricosa ARI00-845 was identified to produce large pollen grains at a low percentage (1.21%). Subsequent analysis using flow cytometry confirmed the presence of 2n gametes in the pollen. Cytogenetic analyses of pollen mother cells revealed cells with twice the typical chromosome number at metaphase I (i.e., 28 chromosomes). We postulate that irregularities in cell wall formation preceding meiosis could have contributed to the mode of chromosome doubling.
Keywords: Flow cytometry; Meiosis; Oats; Pollen mother cells; Unreduced gametes